NATURAL LOW TRANSITION TEMPERATURE MIXTURES (LTTMS) FOR BIOMASS DELIGNIFICATION - YIIN , CHUNG LOONG (2015)
An effective dissociation of lignocellulosic biomass and their subsequent separation are needed for the production of high value products. Low transition temperature mixtures (LTTMs) tend to be the promising green solvents. In this study, low transition temperature mixtures (LTTMs) are prepared from cheap commercially available hydrogen bond acceptor (HBA) and L-malic acid as hydrogen bond donor (HBD) in distinct molar ratio of feedstocks and proportion of water. The physicochemical behaviours of the LTTMs synthesized in water such as hydrogen bonding, thermal stability, glass transition temperature and biopolymers solubility are studied andcompared. The representative peakof carboxylic acid group of malic acid at 1710 cm" for the C=0 group turned broader and the peaks involved in the Hbonding shifted and became broader within 2500-3600 cm"1 for the OH groups with increased molar ratio of water during the preparation of LTTMs. Besides, the thermal properties of the mixtures are not affected by the increased molar ratio of water.